A Complication of Radiotherapy-Oral Mucositis: An Updated Review for Healthcare providers - Alshammari, Salma Raja; Aloteibi, Marzouk Awjin; Aljoufi, Maryam Khalaf; Alharbi, Saab Selayem Saud; Aldosare, Batel Mohamad; Alshehri, Dhafer Sad; Alotaibi, Faris Abdullaha; Alosaimi, Yasser Ayyad Dakhil; Bajafar, Hanan Hmad Salauman; Alenazy, Nouf Garby; Mashreqi, Amal Ibrahim Abdullah; Hayjan, Saad Abdulrazaq Ahmed (Journal of Ecohumanism, 2024)
Oral mucositis (OM) is a debilitating condition characterized by erythema, edema, and ulcerative lesions of the oral mucosa, commonly arising as a complication of radiotherapy (RT), chemotherapy, or hematopoietic stem cell transplantation (HSCT). It significantly impacts patients' quality of life, causing severe pain, nutritional deficiencies, and increased risk of infections, often necessitating treatment modifications.This review aims to provide healthcare providers with an updated understanding of the etiology, pathophysiology, epidemiology, and management strategies for OM, emphasizing evidence-based interventions to mitigate its impact on patients undergoing cancer therapy. This study aims to evaluate the main role of healthcare providers, dentists, and radiologists. The review synthesizes current literature on OM, focusing on its pathogenesis, clinical presentation, diagnostic evaluation, and therapeutic approaches. It highlights the five-phase model of OM development and discusses grading scales such as CTCAE, WHO, and OMAS for assessment. Management strategies, including basic oral care, cryotherapy, low-level laser therapy (LLLT), and chemoprotective agents like palifermin, are evaluated.OM is a multifactorial condition influenced by treatment intensity, patient-specific factors, and mucosal vulnerability. Preventive measures, such as basic oral care and cryotherapy, significantly reduce OM severity. LLLT and palifermin show promise in high-risk populations, though safety concerns remain. Pain management, including topical morphine rinses, improves patient comfort and adherence to therapy. Effective management of OM requires a multidisciplinary approach, integrating preventive strategies, early detection, and tailored interventions. Healthcare providers must prioritize patient education, optimize treatment protocols, and employ evidence-based therapies to minimize OM-related morbidity and enhance treatment outcomes.